THE SUBJECT MATTER AND FUNCTIONS OF POLITICAL CONSULTING - Rubanov, Victor (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2022)
Subject and functions of political consulting are analyzed, which plays rather an important productive and procedural role within the frame of scholarly process aimed at preparing and finally taking crucial political decisions as well as their subsequent implementations. In spite of the fact, its practical use as a scholarly instrument for political decision-making have been yet imperfect, fragmentary, thus it cannot meet the real political necessities of today. Such a state of things is determined, on the one hand, by the significant increase of the subjects of the said process, namely, members of business circles, mass media, profile expertize and analysis centers, specializing in preparatory steps for political decision-making. While, on the other hand, the exact procedural role of political consultants in a very complicated process of new policies emerging has, up to now, been studied dramatically inadequate. Inadequate is, first and foremost, studying political consulting as a classical specialized scholarly instrument, designed not only for optimization of electoral process, market relations in society, but also for working out optimum variants of any political decisions.The purpose of this article is to solve the above-descried scholarly problem, i.e. defining of the subject matter and functions of political consulting as a scholarly subject of political and managerial nature as well as defining its role within the sphere of Political Analysis. All told, the author has analyzed various approaches of other scholars to definitions of political consulting’s essence as a socio-political phenomenon and also as a scientific notion. The author has thoroughly studied exact procedural functions of political consulting as a relatively independent scholarly subject and as an inalienable element of Political Analysis, providing for scientific basis for the preparation of modern political decisions.The said analysis of the problem has resulted in the author’s attempt to determine, within the system of Political Analysis, the exact procedural functions of political consulting as a specialized scholarly subject in the framework of political management, its theoretical and methodological fundamentals, including the sphere of practical politics. The article also defines the exact procedural role of political consulting in the scientifically-based process of preparing political decisions, final decision-making and their practical implementations.